1993
DOI: 10.1002/pssa.2211380237
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence associated with the presence of dislocations in silicon

Abstract: A brief account is given of some recent investigations of the luminescence associated with the presence of dislocations in silicon. These investigations show that transition metal contamination is necessary for dislocation related luminescence to be observed in plastically‐deformed float‐zone silicon and in material containing epitaxial and oxidation‐induced stacking faults. Cathodoluminescence spectroscopy and imaging measurements, and photoluminescence measurements on material with low densities of grown‐in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In contrast to DLTS, there is no such restrictions in photoluminescence (PL). Many studies have been carried out on the defects characterization of crystalline Si using PL [27][28][29][30][31][32]. However, to the best of our knowledge, there has been only one report on the PL of BaSi 2 bulk [33].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to DLTS, there is no such restrictions in photoluminescence (PL). Many studies have been carried out on the defects characterization of crystalline Si using PL [27][28][29][30][31][32]. However, to the best of our knowledge, there has been only one report on the PL of BaSi 2 bulk [33].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the effect of transition metal [3,4] or hydrogen impurities [5,6] has been extensively studied. However, the effect of oxygen has been the object of less attention although it is one of the most important impurities in Si.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of impurities on the DL intensity has been systematically proved by Higgs and coworkers [7,8], who showed that the D1 and D2 luminescence appears only on slightly metallic impurity decorated dislocations in FZ silicon and showed also a straight dependence of DL intensity on transition metal contamination density. DL eventually disappears when metallic impurities segregate as silicides.…”
Section: Introductionmentioning
confidence: 99%